The ‘Other’ in Karl Rahner’s Transcendental Theology and George Khodr’s Spiritual Theology: Within the Near Eastern Context - Avakian, Sylvie (Internationale Theologie / International Theology, 2012)
According to Karl Rahner’s transcendental theology, God is present in the inner reality of every being. Salvation is therefore possible for all. The author proposes a hermeneutical key to be applied on Rahner’s works, based on the assumption that there are two different theological motives or claims in Rahner’s theology. Furthermore the author presents George Khodr’s position concerning the non-Christian religions, particularly Judaism and Islam, within the contemporary Near-Eastern context. Khodr, based on the Patristic heritage of the Eastern Church, makes salvation possible for the ‘Other’ – Christ is the horizon of every human yearning for love and freedom. The ‘Other’ in this sense is the symbol for divine presence in one’s life. It is the very recognition of God, seeing God in the face of the ‘Other’